Cost-effective porous carbon materials synthesized by carbonizing rice husk and K2CO3 activation and their application for lithium-sulfur batteries - Mai, Thanh-Tung (Elsevier, 2019)
In this work, we developed highly porous activated carbon (AC) materials with micro/meso porosity through carbonizing rice husk and treating them with K2CO3. Elemental sulfur was then loaded to the micropores through a solution infiltration method to form rice husk-derived activated carbon (RHAC)@S composite materials. The as-prepared RHAC@S composites with 0.25 mg cm 1 and 0.38 mg cm 1 of sulfur loading were tested as cathodes for lithium-sulfur (Li-S) batteries. The 0.25 mg cm 1 sulfur loaded sample showed an initial discharge capacity of 1080 mA h/g at a 0.1 C rate. After 50 cycles of charge/ discharge tests at the current density of 0.2 C, the reversible capacity is maintained at 312 mA h/g. The RHAC material delivered a capacity of more than 300 mA h/g at a current density of 1.7 C. These results demonstrate that the RHAC porous materials are very promising as cathode materials for the development of high-performance Li-S batteries